PENGARUH BUDAYA ORGANISASI DAN PERILAKU KEPEMIMPINAN TERHADAP KEPUASAN DAN KINERJA PEGAWAI SEKRETARIAT DAERAH KOTA KENDARI. - Nasriah, Nasriah; Madjid, Rahmat; Adam, Laode Bahana (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study are: 1) to examine the effect of organizational culture on employee job satisfaction, 2) to examine the effect of leadership behavior on employee job satisfaction, 3) to examine the influence of organizational culture on employee performance, 4) influence of leadership behavior on employee performance, 5) to assess influence satisfaction with employee performance.The object of this research is the Regional Secretariat of Kendari City. The population of this research is the employees of the Regional Secretariat of Kendari City, amounting to 66 people. The sampling technique uses a census / saturation technique, meaning that all populations are used as samples, thus the study sample is 66 people. Data collection techniques using questionnaires, scale of data measurement using a Likert scale. The research data is analyzed using path analysis with the help of smartPLS 2 software.The results of the study: 1) organizational culture has a positive and significant effect on employee job satisfaction, 2) leadership behavior has a positive and significant effect on employee job satisfaction, 3) organizational culture has a positive and significant effect on employee performance, 4) leadership behavior has a positive and significant effect on employee performance, 5) job satisfaction has a positive and significant effect on employee performance.Â Keywords : Organizational Culture, Leadership Behavior, Satisfaction And EmployeeÂ Â Performance.